Boder's Subtypes of Dyslexia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The subtyping of dyslexic children proposed by Boder (1971, 1973) have been validated by quantitative neurophysiological techniques at the Gunderson Medical Foundation, LaCrosse, WI.